Comparison of knowledge among millennials studying in non-medical universities regarding premarital and prenatal thalassemia screening policies in Pakistan - Shazia Fakhir Durrani; Ammara Hameed; Rida Ali; Inayat Hussain Thaver; Shakeel Ahmed (Journal of the Pakistan Medical Association, 2023)
Thalassemia awareness among the youth is vital for policy-making to reduce the disease burden in our country. A descriptive cross-sectional study was conducted via simple random sampling technique for which data was collected from May 2020 to May 2021 through Google forms. Results showed that out of a total of 394 non-medical university students, the majority, i.e. 265 (67.3%), were not aware of prenatal screening. Majority, i.e. 117 (29.7%), agreed that the couple should be screened before marriage, and 190 (48.2%) strongly agreed, while 46 (11.7%) had no knowledge. Students, however, believed premarital screening was either unavailable, not possible, or expensive. Other reasons included custom and culture of arranged marriages and religious reasons. The query that if both the parents are carriers and the foetus has thalassemia major should they have an abortion, showed mixed results. The key to controlling thalassemia is awareness of future parents.